Gender and Rulership in the Medieval German Empire - Fößel, Amalie (History compass, 2009)
This article discusses queens’ and empresses’ powers, and the changing scope of their activities, in the Medieval German Empire. As a consors regni and partner in politics, queens and empresses played prominent roles in public life and influenced political decisions in the tenth, eleventh and twelfth centuries. Then, in the course of subsequent centuries, the idea of the queens’ partnership in ruling the realm increasingly disappeared. Some of their duties lapsed, while other responsibilities were taken over by the nobility. Queens could still participate in decision making by influencing the King, but more and more they had to carve out a sphere of action for and by themselves. By the later Middle Ages, queens held political power and exercised rulership in the royal family's hereditary territories, but not in the Empire as a whole.